ANALISIS BIAYA PRODUKSI HOME INDUSTRI KERUPUK ELIS BANDUNG - Angelica Dyah Ayu Puspita; Dewi Novita Sari; Noor Laila Fitriana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The purpose of this study is to analyze the production costs of the domestic industry “Elis Bandung” located in Gandekan RT02/RW04, Pucangan, Kartasura, Sukoharjo, Central Java. At the same time, group production costs into direct costs, direct labor costs and manufacturing overhead (BOP). This industrial park was established in 1998. The analysis method includes interviews and data collection for the 2023-2024 season. In this study, the domestic industry divided its employees into production, packaging, frying, baking, administration, drivers, agents, and sales. Production in the small biscuit industry “Elis Bandung” includes kneading, mixing with flour, hydraulicizing the dough, molding, baking, frying, packaging and finally the distribution process. Elis Bandung biscuits have a delicious, attractive flavor thanks to the blend of shrimp juice and meat sauce. This domestic industry is already in operation. Output reaches 80,000 per day and total income 15,000,000 to 25,000,000 per day. From the results of the analysis of the domestic industry, it was concluded that the company